Association between asthma and polyunsaturated fatty acids intake in Brazilian adolescents: study of cardiovascular risk in adolescents-ERICA - Jordão, Érica Azevedo de Oliveira Costa; Felix, Mara Morelo Rocha; Takey, Marcia; Giannini, Denise Tavares; Kuschnir, Maria Cristina Caetano; Kuschnir, Fábio Chigres (Frontiers in Public Health, 2025)
IntroductionPrevious studies have shown that asthma is associated with a less traditional diet pattern with an unbalanced polyunsaturated fatty acids (PUFAs) distribution. This study aimed to investigate the association between asthma and PUFA intake in Brazilian adolescents.MethodsThis is a cross-sectional study, using data from the Study of Cardiovascular Risks in Adolescents-ERICA, a national, school-based multicenter survey with a sample representative of Brazilian adolescents (12–17 years old). The presence of at least one wheezing attack in the last 12 months defined asthma. The intake of the following PUFAs was evaluated: alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), linoleic acid (LA) and arachidonic acid (ARA) as well as N6N3 ratio (the sum of LA and ARA over ALA, DHA and EPA). The odds ratio (OR) and the respective 95% Confidence Interval (95% CI) between asthma and PUFAs intake, as well as other study variables was calculated using Logistic Regression.ResultsA total of 64,904 participants were included for the analysis. After adjustment, asthma remained significantly associated with ALA (OR:1.05; CI95%:1.02–1.09) and EPA (OR:0.61; 95%CI:0.39–0.95), being the first a positive association and the latter a negative one. There were no significant association between asthma and N6N3 ratio, as well as the other PUFAs evaluated.ConclusionOur findings reveal a higher chance of asthma among Brazilian adolescents with increased ALA consumption and, elevated intake of EPA was associated with decreased odds.